2019
DOI: 10.3390/ijfs7030043
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of FDI in Sub-Saharan Economies: A Study of Data from 1990–2017

Abstract: Foreign Direct Investment (FDI) can bring in much needed capital, particularly to developing countries, help improve manufacturing and trade sectors, bring in more efficient technologies, increase local production and exports, create jobs and develop local skills, and bring about improvements in infrastructure and overall be a contributor to sustainable economic growth. With all these desirable features, it becomes relevant to ascertain the factors which attract FDI to an economy or a group of adjacent economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 37 publications
4
41
0
1
Order By: Relevance
“…FDI in Africa predetermines the faith of innovation. Thus, innovation can be improved with the provision of adequate FDI through the appropriate means (Jaiblai and Shenai 2019). Loukil (2020) emphasized that financial resources are the direct element of technological development.…”
Section: The Role Of Fdi Trade and Financial Development On African Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…FDI in Africa predetermines the faith of innovation. Thus, innovation can be improved with the provision of adequate FDI through the appropriate means (Jaiblai and Shenai 2019). Loukil (2020) emphasized that financial resources are the direct element of technological development.…”
Section: The Role Of Fdi Trade and Financial Development On African Innovationmentioning
confidence: 99%
“…However, unlike African countries, the export of high-tech export is insignificant hence, most African countries heavily dependent on the importation of high-tech products from developed nations (Bayraktutan and Bıdırdı 2018). Other studies (Asiedu 2002;Jaiblai and Shenai 2019) have also indicated that, African countries receive FDI as a form of technology development. This, consequently, highlights the impact of FDI on the development of African countries instead of the exportation of technology from African.…”
Section: The Impact Of Fdi On Innovation High Tech Export and Information Tech Exportmentioning
confidence: 99%
“…Hal ini karena infrastruktur merupakan prasarana publik primer dalam mendukung kegiatan ekonomi Indonesia, dan keterse-diaan infrastruktur sangat menentukan tingkat efisiensi dan efektivitas kegiatan ekonomi. Infrastruktur diartikan sebagai layanan utama dari suatu negara yang dapat menunjang keberlangsungan kegiatan masyarakat dan kegiatan ekonomi dengan menyediakan transportasi dan fasilitas pendukung lainnya (Jaiblai & Shenai, 2019). Infrastruktur yang memadai di Indonesia akan mengakibatkan efisiensi pada dunia usaha, sehingga investasi yang didapat semakin meningkat.…”
Section: Hasil Dan Pembahasanunclassified
“…There is a lack of study focusing on the consequence of FDI on different variables like growth, finance, economic development, North vs the South convergence, etc. (Alfaro & Chauvin, n.d.;Demena, n.d.;Demir & Duan, 2018;Dupasquier & Osakwe, 2006;Eddine, n.d.;Elkhuizen et al, 2018;Francis et al, 2009;Hallam, 2011;Hausmann & Fernández-Arias, n.d.;Herzer et al, 2008;Jaiblai & Shenai, 2019;Kose et al, 2009) Most of these studies absorbed on the spillover special effects of FDI on the economies. Many studies also focused on the spillover effect of FDI on productivity (Ajide & Raheem, 2016;Albuquerque, 2003;Bhattacharyya, 2012;Cleeve, 2008;Kose et al, 2009;Nunnenkamp, 2001;Singh, 2003).…”
Section: Gap Analysismentioning
confidence: 99%